Optimal Strategy for the Improvement of the Overall Performance of Dual-Axis Solar Tracking Systems - Diego A. Flores-Hernández (MDPI AG, 2021)
Solar Tracking Systems are useful to increase the generation efficiency of photovoltaic technology, mainly for concentration technology, where dual-axis is required on account of the high accurate alignment to the Sun. Even when there exists a strong relation between tracking error and energy efficiency, multiple technological and research developments have sought to solve these problems independently. The present research proposes a novel concurrent design methodology for optimizing the overall performance of two-axis trackers, allowing to keep a balance between the tracking error and the energy consumption from the design stage, from an optimization approach. The concurrent approach was implemented to design a Solar Tracker as a solar monitoring system, was compared with four commercial systems, obtaining a similar pointing accuracy with a mixed tracking error of <semantics>0.0942°</semantics>. The system has the best energy balance, consuming only <semantics>0.9641%</semantics> of the energy generated for the tracking action, below commercial models. Finally, a CO<semantics>2</semantics> impact analysis was carried out, where the proposed tracker obtained the lowest value, with <semantics>25.7018</semantics> g. The results support the developed concurrent strategy for the optimization of the overall performance of dual-axis systems, allowing us to find a harmonic balance between the energy consumption and the required tracking accuracy.